Diagnosis and treatment of Merkel cell carcinoma: European consensus-based interdisciplinary guideline – Update 2022 - Gauci, Marie-Léa; Aristei, Cynthia; Becker, Jurgen C.; Blom, Astrid; Bataille, Veronique; Dreno, Brigitte; Del Marmol, Veronique; Forsea, Ana M.; Fargnoli, Maria C.; Grob, Jean-Jacques; Gomes, Fabio; Hauschild, Axel; et al. (European journal of cancer (1990), 2022)
Merkel cell carcinoma (MCC) is a rare skin cancer, accounting for less than 1% of all cutaneous malignancies. It is found predominantly in white populations and risk factors include advanced age, ultraviolet exposure, male sex, immunosuppression, such as AIDS/HIV infection, haematological malignancies or solid organ transplantation, and Merkel cell polyomavirus infection. MCC is an aggressive tumour with 26% of cases presenting lymph node involvement at diagnosis and 8% with distant metastases. Five-year overall survival rates range between 48% and 63%. Two subsets of MCC have been characterised with distinct molecular pathogenetic pathways: ultraviolet-induced MCC versus virus-positive MCC, which carries a better prognosis. In both subtypes, there are alterations in the retinoblastoma protein and p53 gene structure and function. MCC typically manifests as a red nodule or plaque with fast growth, most commonly on sun exposed areas. Histopathology (small-cell neuroendocrine appearance) and immunohistochemistry (CK20 positivity and TTF-1 negativity) confirm the diagnosis. The current staging systems are the American Joint Committee on Cancer/Union for international Cancer control 8th edition. Baseline whole body imaging is encouraged to rule out regional and distant metastasis. For localised MCC, first-line treatment is surgical excision with postoperative margin assessment followed by adjuvant radiation therapy (RT). Sentinel lymph node biopsy is recommended in all patients with MCC without clinically detectable lymph nodes or distant metastasis. Adjuvant RT alone, eventually combined with complete lymph nodes dissection is proposed in case of micrometastatic nodal involvement. In case of macroscopic nodal involvement, the standard of care is complete lymph nodes dissection potentially followed by post-operative RT. Immunotherapy with anti-PD-(L)1 antibodies should be offered as first-line systemic treatment in advanced MCC. Chemotherapy can be used when patients fail to respond or are intolerant for anti-PD-(L)1 immunotherapy or clinical trials. •Major progress in the diagnosis of Merkel cell carcinoma by immunohistochemistry/molecular pathogenesis.•The management of primary tumour was mostly based on retrospective studies.•Breakthrough in advance disease management with the approval of immunotherapy.